KEANEKARAGAMAN TUMBUHAN PAKAN SIAMANG (Symphalangus syndactylus) DI STASIUN PENELITIAN SORAYA KAWASAN EKOSISTEM LEUSER KOTA SUBULUSSALAM - Malahayati, Cut; Hidayat, Muslich; Ahadi, Rizky (KENANGA : Journal of Biological Sciences and Applied Biology, 2025)
Symphalangus syndactylus is a long-armed primate that plays a crucial ecological role as a pollinator and seed disperser. However, this species is currently classified as endangered. According to the IUCN (International Union for Conservation of Nature) in 2021, Siamang populations have been declining due to extensive deforestation, which has reduced the availability of their natural food sources.This study aimed to identify the diversity of plant species consumed by Siamangs. We conducted an exploratory survey using the line transect method across three trails. Data on food plants were collected along 1000-meter transects in each trail. Plant diversity was analyzed using the Shannon-Wiener diversity index (H' = -∑ Pi ln Pi).The results revealed 56 species of food plants from 22 families. The overall diversity index value of H'=2.74 indicates that the diversity of Siamang food plants at Soraya Research Station is at a moderate level. Keywords: Food plants diversity, Siamang, Soraya Research Station, Subulussalam